(untitled) (Bangladesh Journal of Pharmacology, 2010)
Quest is still going on for a cheap, effective, and easily available remedy for chronic arsenic toxicity. This study was designed to investigate the effects of folic acid and tetrahydrofolate in lowering the arsenic burden in tissues. Rats received arsenic at 700 µg/day by gavage for 28 days except the control group. Arsenic accumulation was significantly lowered (p<0.05), in liver, kidney, heart, lung and skin in both the folic acid and tetrahydrofolate-treated groups compared to arsenic only treated group. The oxidative stress induced by arsenic treatment was reduced as evident by the reduction in rise of malondialdehyde level in both groups. But folic acid was found to be more efficacious compared to tetrahydrofolate.